Analyses of MT1-MMP activity in cells. - Evans, R; Itoh, Y (2007)
Membrane-type 1 matrix metalloproteinase (MT1-MMP) is a type I transmembrane protein which exhibits biological activities on the cell surface. One of the characteristic functions of this enzyme is activation of proMMP-2 on the cell surface (1). This process can be monitored using gelatin zymography to detect the pro- and active forms of MMP-2. Cellular MT1-MMP activity can also be directly detected by in situ degradation of layers of either gelatin or collagen. By combining inhibitors, western blotting, and immunohistochemistry, one can detect and conclude the presence of MT1-MMP activity in the cells.